Isolation, Identification, and Activity Test of Flavonoid Compounds in Jamblang Leaves (Syzygium cumini L.) Skeel - Jatmiko, Miracela Putri; Mursiti, Sri (Universitas Negeri Semarang, 2021)
Jamblang (Syzygium cumini L.) Skeel is a plant that has the potential to be a natural antioxidant. The jamblang plant contains chemical compounds including alkaloids, flavonoids, resins, tannins, and essential oils. This study aims to identify the class of flavonoid compounds contained in jamblang leaves using a spectrophotometer UV-Vis and FTIR and to determine the antioxidant activity of jamblang leaf determined by the percentage of resistance. Determination result of antioxidant activity in ethanol extract, ethyl acetate and isolate of jamblang leave against ABTS (2,2-azino-bis(3-etilbenzotiazolin)-6-asam sulfonat) the highest percentage was shown at 40 ppm of ethyl acetate extract equal is 46,77%. The Identification results of isolate jamblang leave contained flavonoid compounds from the flavonol groups.